FISCAL MANAGEMENT IN KERALA: CONSTRAINTS AND POLICY OPTIONS - K.K.George K.K.Krishnakumar (CSESWP9, 2003)
States in India with the exception of a few Special Category States and the National Capital Territory of Delhi have been reeling under severe fiscal crisis from the middle of the eighties.1 As for Kerala, its fiscal distress dates back to a much earlier period. Kerala had incurred budgetary deficits in its revenue and capital accounts as far back as in the Fifth Five Year Plan period (1975-76 & 1976-77). The amounts involved were, however, small. During the Sixth and the Seventh Plan periods (1980-90), Kerala had overall deficits during four years each. The amounts involved became larger.2 During the eleven year period ended in 2000-01, which coincided with the post-liberalisation period with all its emphasis on containing budgetary deficits, Kerala had deficits during six years (See Table 1). Revenue deficits became a continuous phenomenon for Kerala from 1983-84 onwards while the phenomenon appeared only from 1987-88 for other States taken as a group (hereafter referred as All States).